Identification and Fine Mapping of a Mutation Conferring Salt‐Sensitivity in Rice (Oryza sativa L.). Issue 1 (1st January 2015) - Deng, Ping; Shi, Xingyu; Zhou, Jingwei; Wang, Fuzheng; Dong, Yanmin; Jing, Wen; Zhang, Wenhua
ABSTRACT: Single‐gene mutants tolerant or sensitive to salt stress are ideal materials for identifying and cloning genes related to salt tolerance in rice ( Oryza sativa L.). In the present study, a salt‐sensitive mutant was obtained from the ethyl methanesulfonate (EMS)‐induced Nipponbare bank. The mutant, designated rice salt sensitive 4 ( rss4 ), showed a significant increase in salt sensitivity at the seedling stage and accumulated high levels of Na + in shoots, particularly in the blades of old leaves, under conditions of NaCl stress. Genetic analysis indicated that the mutation was controlled by a single recessive gene. Quantitative trait locus (QTL) analysis for shoot Na + content was performed using an F2 population derived from a cross between the rss4 mutant and the indica cultivar Zhaiyeqing 8 (ZYQ8). Three QTLs were identified and one located on the long arm of chromosome 6 was determined to be the candidate locus of the rss4 gene based on comparison and analysis, which explained 40.5% of the phenotypic variance in the shoot Na + content of the F2 population. Further analysis of recombination events in 165 mutant individuals of an enlarged mapping population of rss4 /ZYQ8 defined the rss4 locus to an interval of 230.5 kb bracketed by markers RM20566 and IM28706 on chromosome 6.